The application domain of difference type matrix D(r,0,s,0,t) on some sequence spaces - Paul Avinoy; Tripathy Binod Chandra (Yugoslav Journal of Operations Research, 2021)
We say that a regular graph G of order n and degree r ≥ 1 (which is not the complete graph) is strongly regular if there exist non-negative integers τ and θ such that |Si ∩ Sj | = τ for any two adjacent vertices i and j, and |Si ∩ Sj | = θ for any two distinct non-adjacent vertices i and j, where Sk denotes the neighborhood of the vertex k. Let λ1 = r, λ2 and λ3 be the distinct eigenvalues of a connected strongly regular graph. Let m1 = 1, m2 and m3 denote the multiplicity of r, λ2 and λ3, respectively. We here describe the parameters n, r, τ and θ for strongly regular graphs with m2 = qm3 and m3 = qm2 for q = 7/2 , 7/3 , 7/4 , 7/5 , 7/6 .